Operative Management of Hilar Renal Artery Aneurysm in a Pregnant Patient - Schulte, Wibke (Ann Vasc Dis, 2015)
Complications of renal artery aneurysms (RAAs) can be life threatening and include the spontaneous rupture which may lead to severe retroperitoneal hemorrhage, loss of the kidney, or death. As the incidence and diagnosis of RAAs is expected to rise, it is becoming increasingly important to enhance our awareness and knowledge of this rare clinical entity. Here, we present the case of a hilar right RAA and the surgical approach for primary repair during the postpartum period. Additionally, we discuss current pathophysiologic mechanisms, associated symptoms as well as current treatment modalities for RAAs.